Oil in Asia : markets, trading, refining and deregulation - Horsnell, P (Oxford Institute for Energy Studies, 1997)
The twenty-first century has been dubbed, even before its advent, as the Pacific century. While perhaps still premature, the epithet is representative of a general perception that the centre of the world economy is increasingly moving towards the Asia-Pacific region, and the distribution of economic power is steadily moving away from Europe and the USA. This study is concerned with one aspect of this transition, the impact on the energy industries and in particular oil.